SUSTAINABILITY OF TOURISM MANAGEMENT: MANAGING WASTE OF TOURISM INDUSTRY IN KELANTAN - Noorulfarahiah Binti Ismail; Dr. Hasif Rafidee Bin Hasbollah (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This paper will focus on the sustainability tourism management in the waste management aspect in Kelantan. Kelantan is used as the main subject place because of the lack of study in managing waste. Sustainable tourism and waste management are explored in this paper. Through the Malaysia Local Agenda 21, the sustainable development is the whole responsibility of Malaysian in order to make it happen. The best practice in waste management for accommodation and camping site are also discussed in this paper.